Using a Typological Approach in Conducting Local Economic Policy (By The Example of the Gatchina District of Leningrad Region) - Valery Igorevich Belov (Управленческое консультирование)
The article proposes use of the typological approach to improving the management of municipalities. Separating own criteria typology of settlements and the steps of creating a typological groups, the author generates typological groups of municipalities Gatchina district of the Leningrad region, which will further promote the development of model-making.